Recipe for Heart Health: A Randomized Crossover Trial on Cardiometabolic Effects of Extra Virgin Olive Oil Within a Whole‐Food Plant‐Based Vegan Diet - Andrea M. Krenek; Anne Mathews; Juen Guo; Amber B. Courville; Carl J. Pepine; Stephanie T. Chung; Monica Aggarwal (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Whole‐food, plant‐based vegan diets, low in oils, and Mediterranean diets, rich in extra virgin olive oil (EVOO), reduce cardiovascular disease risk factors. Optimal quantity of dietary fat, particularly EVOO, is unclear. Methods and Results In a randomized crossover trial with weekly cooking classes, adults with ≥5% cardiovascular disease risk followed a high (4 tablespoons/day) to low (<1 teaspoon/day) or low to high EVOO whole‐food, plant‐based diet for 4 weeks each, separated by a 1‐week washout. The primary outcome was difference in low‐density lipoprotein cholesterol (LDL‐C) from baseline. Secondary measures were changes in additional cardiometabolic markers. Linear mixed models assessed changes from baseline between phases, with age, sex, and body weight change as covariates. In 40 participants, fat intake comprised 48% and 32% of energy during high and low EVOO phases, respectively. Both diets resulted in comparable reductions in LDL‐C, total cholesterol, apolipoprotein B, high‐density lipoprotein cholesterol, glucose, and high‐sensitivity C‐reactive protein (all P<0.05). With diet‐sequence interactions for LDL‐C, differences were detected between diets by diet order (mean±SEM high to low: Δ‐12.7[5.9] mg/dL, P=0.04 versus low to high: Δ+15.8[6.8] mg/dL, P=0.02). Similarly, low to high order led to increased glucose, total cholesterol, and high‐density lipoprotein cholesterol (all P<0.05). Over period 1, LDL‐C reductions were −25.5(5.1) post‐low versus −16.7(4.2) mg/dL post‐high EVOO, P=0.162, which diminished over period 2. Conclusions Both plant‐based diet patterns improved cardiometabolic risk profiles compared with baseline diets, with more pronounced decreases in LDL‐C after the low EVOO diet. Addition of EVOO after following a low intake pattern may impede further lipid reductions. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT04828447.